ВІТЧИЗНЯНІ РЕАЛІЇ ПЕРЕСТРАХУВАННЯ - Kucherivska, Sofia; Ольга, Гладчук (My University, 2020)
Reinsurance is a guarantor and catalyst for the development of the insurance market, it increases its capacity and financial security. The aim of the article is to study the current trends of reinsurance in Ukraine, identify the main problems in their implementation and formulate appropriate areas for their solution. The works of domestic and foreign scientists in the field of reinsurance have become a theoretical and informational basis for writing the article. This study was conducted by implementing methods of analysis and synthesis, theoretical generalization, comparative analysis, statistical and graphical methods. There is no single approach among Ukrainian reinsurance researchers regarding the use of basic reinsurance terms. It is important to use the correct reinsurance terminology, which is clearly defined in Ukrainian legislation, distinguishing between the concepts of "actions of the primary reinsurer" and "actions of the reinsurer" in reinsurance. At present, domestic insurers mostly reinsure their risks in "parent companies" or foreign reinsurers, paying almost a third of the reinsurance premiums involved. Ukrainian reinsurance is characterized by the fact that reinsurance premiums are paid mainly to resident reinsurers, while the majority of insurance payments are made by non-resident reinsurers. Domestic insurers are reinsuring the risks of primary non-resident insurers, but this activity is not yet so successful. A potential direction for the further development of reinsurance in Ukraine is the creation by the state, or with its participation, of a national reinsurance company or a Ukrainian reinsurance pool using modern financial products and technological innovations. As a result of the transfer of powers to supervise the activities of insurers to the NBU, we can expect effective changes in the legislative provision of insurance and reinsurance activities based on world experience, implementation of Solvency II and improving the quality of insurance and reinsurance activities by insurance market participants.
Keywords: страхування; перестрахування; перестрахова діяльність; перестраховик; перестрахувальник; перестрахова премія; перестрахова виплата; вхідне перестрахування; вихідне перестрахування; забезпечене перестрахування